BS EN IEC 62803-2. Transmitting and receiving equipment for radiocommunication. Frequency response of optical-to-electric conversion device in high-frequency radio over fibre systems. Part 2. Measurement method of common-mode rejection ratio of optical coherent detection device for radio over fibre transmitter (5th November 2021) - British Standards Institution,
No abstract available